Application of AudioVisual Media in Physical Fitness Learning for Elementary School Students: media audio visual - Pratiwi, Maryati; Solahudin, Aang; Maria, Sinta (Indonesian Journal of Sport Management, 2024)
This research aims to describe the application of audio visual media which can influence students in physical fitness activities in elementary schools. The subjects of this research were physical education teachers and class III students at Al-furqon Islamic Elementary School for the 2023/2024 academic year, totaling 2 students. The instruments of this research are observation, interviews and documentation. The results of this research show an increase in students' physical fitness levels in the application of audio-visual media in elementary schools. Thus, it can be concluded that the application of audio visual media can influence students in physical fitness activities in elementary schools and increase student participation in physical fitness learning activities in elementary schools.